Patriots Against Fashion - Maxwell, A. author. aut Link
IX, 311 p.
Keywords: During the era of the French revolution, patriots across Europe tried to introduce a national uniform. This book, the first comparative study of national uniform schemes, discusses case studies from Austria, Bulgaria, England, France, Germany, Hungary, Italy, the Netherlands, Spain, Sweden, Turkey the United States, and Wales.